Exploring the surface of Trypanosoma brucei through protein sorting and recombinant expression - Miller, Thomas (2020)
Surface membrane structure and composition define the biological niche of a unicellular organism, controlling how it interacts with and survives in its environment. The human and animal pathogen Trypanosoma brucei lives extracellularly in the blood of its mammalian host, where it must evade continual surveillance by the immune system whilst obtaining nutrients required for survival. It achieves this through antigenic variation of its major surface protein (the glycosylphosphatidylinositol (GPI)-anchored VSG) and surface compartmentalisation, retaining transporters and receptors essential for the uptake of nutrient in a specialised membrane invagination at the base of its flagellum – the flagellar pocket (the sole site of endocytosis and secretion in the parasite). This PhD exploits a high-confidence, validated cell surface proteome (‘surfeome’) for bloodstream-form T. brucei to test hypotheses about GPI-anchored protein sorting and flagellar pocket retention. It also attempts to contribute towards early-stage development of strategies for disease control through the recombinant production of surfeome components for testing as vaccine candidates.